Evaluation of the antiviral effect of four plant polysaccharides against duck circovirus. (20th December 2022) - Wang, Xiangkun; Zhang, Shuyu; Shang, Hongqi; Wang, Cheng; Zhou, Fan; Liu, Yong; Jiang, Yunxuan; Gao, Panpan; Li, Ning; Liu, Defeng; Shen, Mingyue; Zhu, Ruiliang; et al.
Abstract: Recently, outbreaks of duck circovirus (DuCV) are frequently occurring worldwide due to secondary infections caused by post infection-induced immunosuppression. Due to a lack of preventive drugs and vaccines, the waterfowl industry losses are ever increasing. In this study, we extracted Astragalus polysaccharides (APS), pine pollen polysaccharides (PPPS), Aloe vera polysaccharides (AVE), and Ficus carica polysaccharides (FCPS) from Astragalus, pine pollen, aloe, and F. carica leaves, respectively. We randomly divided 150 one-day-old Cherry Valley ducks into five groups, which were inoculated with the DuCV solution and orally administered APS, PPPS, AVE, FCPS, and phosphate buffer saline (PBS), respectively. We collected the duck immune organs and serum samples at 8, 16, 24, 32, 40, and 48 days post-infection (dpi). Using clinical symptom analysis, molecular biology experiments, and serological experiments, we proved that plant polysaccharides could (a) improve the duck immunity, (b) reduce the viral load, and (c) mitigate DuCV-induced damage to immune organs, with both APS and PPPS having significant effects. Moreover, we detected viral load and cytokines within the first 8 dpi. Since the body's innate immunity could inhibit viral replication within five days of virus infection, 1–5 dpi was the best treatment time. Among the four polysaccharides showing in vitro anti-apoptotic activity, APS and PPPS significantly inhibited the DuCV infection-induced apoptosis of peripheral blood lymphocytes. Overall, since our findings show APS and PPPS having significant anti-DuCV effects both in vivo and in vitro, they can be promising candidates for preventing DuCV infection in ducks. Highlights: The polysaccharides exerted antiviral activity against DuCV, both  in vivo  and  in vitro . The best time for administering these antiviral polysaccharides is during the 5 dpi. APS and PPPS have better anti-DuCV effects than AVE and FCPS.